Investing in the Trump Era How Economic Policies Impact Financial Markets - Sargen, Nicholas P. (Springer International Publishing, 2018)
In the wake of the 2016 U.S. presidential election, investors and the electorate alike are seeking clarity on a wide range of macro policy issues that will impact the economy and markets in the years ahead. The primary goal of this book is to provide an objective source for investors to learn about economic policy issues that surfaced. Topics include long-term growth, the federal budget deficit, healthcare reform, tax reform, regulatory policies affecting the financial system and environment, the nexus of monetary, exchange rate and trade policies, and globalization. The book explains how these issues have evolved, considers arguments from both sides of the political divide, and draws upon evidence from studies by experts in the respective areas. A related goal is to assess the likely impact of economic policies on financial markets. While the presidential election was close, the markets' response was decisive: U.S. and global equity markets went on a tear as consumer and business confidence soared. This surprised many investors who believed a Trump victory would be bad for financial markets. It also caused many to question whether expectations embedded in markets were too optimistic. Sargen's assessment is presented in the opening and concluding chapters. .